2022
DOI: 10.1590/1678-7757-2022-0086
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of bone morphogenetic protein-7 and mineral trioxide aggregate on the proliferation, migration, and differentiation of human dental pulp stem cells

Abstract: Combined effects of bone morphogenetic protein-7 and mineral trioxide aggregate on the proliferation, migration, and differentiation of human dental pulp stem cellsBioactive molecules present the potential to be used along with biomaterials in vital pulp therapy and regenerative endodontic treatment. Objective: The aim of this study was to assess the effects of the combined use of bone morphogenetic protein-7 (BMP-7) and mineral trioxide aggregate (MTA) on the proliferation, migration, and differentiation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
1
0
3
Order By: Relevance
“…O propósito da abordagem terapêutica para a polpa dentária vital, engloba técnicas como capeamento pulpar direto, curetagem pulpar (pulpotomia parcial) e pulpotomia, que consistem em manter a vitalidade do tecido pulpar (KÜÇÜKKAYA EREN et al, 2022).…”
Section: Referencial Teóricounclassified
See 2 more Smart Citations
“…O propósito da abordagem terapêutica para a polpa dentária vital, engloba técnicas como capeamento pulpar direto, curetagem pulpar (pulpotomia parcial) e pulpotomia, que consistem em manter a vitalidade do tecido pulpar (KÜÇÜKKAYA EREN et al, 2022).…”
Section: Referencial Teóricounclassified
“…Nos períodos recentes, o emprego de biomateriais tem ganhado relevância devido à sua notável biocompatibilidade, capacidade bioativa e eficaz selamento, sendo utilizados nos tratamentos conservadores da polpa (KÜÇÜKKAYA EREN et al, 2022).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Emblematic of factors eventually present on the ECM is the example of stromal cellderived factor 1 (SDF1), which is a chemokine released by injured tissues as brain, hearth and bone. In vitro studies showed that SDF1 improved DPSC migration [15,40] and in combination with other chemo-attractants such as bone morphogenetic protein 7 (BMP-7), parathyroid hormone (PTH) and exendin-4 (EX-4), improved the efficiency of the osteogenic differentiation of DPSC and periodontal ligament stem cells (PDLSC) [18,41,42,117]. Other growth factors, such as glial cell-derived neurotrophic factor (GDNF) [22] and insulin-like growth factor-binding protein 5 (IGFBP5), promoted DPSC migration and enhanced the osteo/odontogenic and neurogenic differentiation of DPSCs [43].…”
Section: The Hdpsc Fatementioning
confidence: 99%